Research on the relationship between marital commitment, sacrifice behavior and marital quality of military couples - Lemin Lin; Hang Guo; Lisa Duan; Li He; Chaoliang Wu; Zhangya Lin; Jiangnan Sun; Jiangnan Sun (Frontiers in Psychology, 2022)
Based on the actor-partner interdependence model, this paper studied the relationship between marital commitment, sacrifice behavior and marital quality of military couples. A convenience sample of 171 Chinese military couples from Guangdong, Jiangsu and Sichuan province was used. All participants completed the self-report questionnaires independently including the Dimension of Commitment Inventory (DCI), the Couples Sacrifice Behavior Scale (CSBS) and the Evaluation and Nurturing Relationship Issues, Communication and Happiness (ENRICH). Results showed that the scores of marital commitment and marital quality of male soldiers were significantly higher than that of their spouses. Compared to their spouses, male soldiers reported higher frequency of sacrifice behaviors and perceiving sacrifice behaviors of spouses. Furthermore, the marital commitment of military couples had significant influence on their own marital quality and frequency of perceiving each other’s sacrifice behavior Military couples’ perception of the frequency of each other’s sacrifice behavior partially mediated the effect of marital commitment on their marital quality. Male soldiers’ perception of spouse’s sacrifice behavior frequency significantly predicted the marital quality of their spouses.